Effect of losal water flooding on w/o emulsions stability - Sarmas Farfan, Jordy Jamil (2019)
The continued depletion of crude oil reservoirs and the lack of new oilfields discoveries have encouraged the countries, whose economies depend on crude oil, to implement enhanced oil recovery (EOR) techniques. Low salinity (LoSal) water flooding is an EOR technique that has gained great importance because of its potential for use and the simplicity of its application. Investigations on this subject attribute the enhanced oil recovery action, shown by low salinity water flooding, to several mechanisms related to substrate/crude/brine interactions, including emulsion flow. Emulsions are useful in enhanced oil recovery because they can act as mobility control agents that improve the efficiency of the injected fluid. In the present work, the emulsifying capacity of a representative sample of an Amazonian-Ecuadorian crude oil, selected from Campo Sacha, was evaluated. A set of five activities was proposed: a) the first activity consisted on contrasting the crude oil recovery during high and low salinity water flooding through a computational simulation in Computer Modelling Group (CMG-IMEX) software; b) the following three activities consisted on evaluating the effect of salinity reduction, cation type and temperature on emulsion stability by using bottle tests and water separability apparatus; c) for the last activity, optical microscopy and software Image J were used for analyzing the morphology of the generated emulsions. Results obtained by computational simulation showed that crude oil recovery is higher during low salinity water flooding than during high salinity water flooding. Experimentally, it was determined that more stable macroemulsions with a better dispersion of phases is accomplished by the reduction of aqueous phase salinity and by the increment of divalent cations concentration, such as calcium and magnesium. On the other side, using the modified ASTM D1401 norm, it was observed that low temperatures also lead to more stable macroemulsions. Finally, it can be concluded that crude oil from Campo Sacha responds positively to low salinity water flooding in terms of emulsions strengthening and consequently, there is potential for local enhanced oil recovery processes application.